AI and multimedia: a synergy of color and image innovation - Abu-Jassar Amer Tahseen; Al-Jamal Ehab Zuhair (ТОВ «Друкарня Мадрид», 2024)
In the digital age, artificial intelligence (AI) has become a pivotal force in enhancing multimedia technologies. This work explores the dynamic integration of AI with multimedia, focusing on advancements in color and image recognition technologies. Through the lens of recent research , we analyze how AI-driven techniques are revolutionizing the perception and interaction with multimedia content, enabling more intuitive and engaging user experiences.
Keywords: artificial intelligence; color